Two Incredible Summation Formula Involving Computational Technique (Global Journal of Science Frontier Research, 2015)
In this paper, we have established two summation formulae with the help of contiguous relation and some derived formulae of Salahuddin et al.
Keywords: contiguous relation; summation formulae